Catalogue of the vascular plants frorn the Ciudad Universitaria de Madrid (Spain) - Casas, Inmaculada; Gavilán, Rosario; Echevarría, Juan E. (Botanica Complutensis, 1993)
GAvILAN, R., EcHEvARRíA, JE. & CAsAs, 1. 1992. Vascular tloristic catalogue of the Ciudad Universitaria of Madrid (Spain). Bat. Cotnplutensis 18: 175-201 A list of 421 taxa belonging to 52 families, from the Ciudad Universitaria of Madrid (Spain) is presented. Spontaneous, naturalized and adventitious plants have been recorded. Life-form, chorological area, soil type and phytosociological characterization are reponed for each species. The results show that therophytes are the most abundant, probably due to the anthropic influence. Mediterranean elements have been found having similar presence than those with wider distribution (Cosmopolitan, Eurasiatic, ..). Most of the taxa are indifferent to geological substratum. Ruderal and annual are the most common community types. It must be also remarked that some of tho.se taxa have probably dissapeared from this area because of works on the M-30 ring road. Finally, a selected list of pedo-indicators taxa is included. Este trabajo se ha realizado en el marco del Proyecto de Investigación financiado por la Consejería de Educación de la Comunidad de Madrid n’ CO 12/90. Botánica Complutensis 18:175-201. Edit. Universidad Complulense 1993 176 Rosario Gavilán, man E. Echevarría & lnntarulada Casas